ANALYZING MUSIC IN TV SHOWS: SOME METHODOLOGICAL CONSIDERATIONS / АНАЛИЗ МУЗЫКИ В ТЕЛЕВИЗИОННЫХ СЕРИАЛАХ: НЕКОТОРЫЕ МЕТОДОЛОГИЧЕСКИЕ СООБРАЖЕНИЯ - PIOTROWSKA ANNA G. / ПИОТРОВСКА АННА (Наука телевидения, 2018)
The growing popularity of TV serials (broadly defined as multi-episode TV productions of various character) goes along with the rapidly expanding reputation of music accompanying such shows. We can talk about the international success of several soundtracks. Recognizing this situation, the article prompts undertaking profound studies on music featured in TV shows suggesting analytical procedures embracing three, interdependent perspectives: referring to one episode, to a musical scene/sequence and to the whole serial understood as a cohesive entity. The first approach is of normative character and involves gauging the length of musical fragments versus the length of the episode, measuring how often and determining where musical fragments appear, checking the patterns of their distribution with the episode, etc. We also need to identify characteristic musical (leit) motifs (most specifically the central motif, usually the one opening all episodes) and divide musical fragments into those of diegetic and non-diegetic character. While discussing scenes or sequences with musical components, we focus on musical solutions assessing to what extent they are (a)typical for the whole serial. The third stage involves an attempt to look at music in all episodes as a structural element of the whole serial, as well as is aimed at answering the question concerning the functions which music plays in a particular serial. The article is deeply rooted in the tradition of Film Musicology making use of its terminology, concepts, definitions as well as analytical tools. The theoretical framework provided in the article is designed as a modest proposal for musicologists and film specialists alike, as well as all those interested in musical and sonic aspects of TV shows, who can also develop their own, methodological approaches to music in TV shows.